Genetic Diversity in Bioinformatics: A Novel Application of Biology - Bhambri, Pankaj; Gupta, Dr. O.P. (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
This paper deals with the various search and analysis techniques involving different possible pairs of varieties selected on the basis of morphological characters, Climatic conditions and Nutrients so as to obtain the optimal pair that can produce the required crossbreed variety. An algorithm has been developed to determine the genetic diversity between the selected wheat varieties. Data mining techniques have been used for retrieving the results. Dummy values have been assumed wherever actual data was not available. MATLAB has been deployed to demonstrate the results in a better visual perspective.